Proces tarnopolski z 1895 roku - Koredczuk, Józef (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
In 1895 one of the most famous political trials in Galicia at the end of the 19th century took place in Tarnopol. Twenty-six people were accused of the crime of treason, insulting majesty and disturbing the peace. The main accused was Wacław Borzemski, a well-known activist of independence organizations. A men’s teacher seminar in Tarnopol was the center of the underground movement, whose participants were the accused. After a thirteen-day trial, thanks to the use of legal possibilities offered by the law on court proceedings, all the accused were acquitted. This trial had a broad resonance in the Galician press at the time, and was of great importance for Polish organizations in Galicia undertaking the struggle for Polish independence in the late 19th and early 20th centuries.
Keywords: organizacje niepodległościowe; seminarium nauczycielskie w Tarnopolu; Tarnopol; Borzemski, Wacław (1868-1935); zdrada stanu